2016
DOI: 10.1111/iep.12212
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation of ATP‐binding cassette B1 (ABCB1) multidrug resistance 1 (MDR1) is associated with cisplatin resistance in the A549 lung adenocarcinoma cell line

Abstract: Development of multiple drug resistance has been attributed to the overexpression of the ATP-binding cassette B1 (ABCB1) gene. In this study, the major purpose was to assess the expression and methylation levels of ABCB1 in human lung adenocarcinoma and to reveal the relationship between these processes and acquisition of cisplatin (DDP) resistance in the human cancer cell line A549. Methylation and expression levels of the ABCB1 gene ABCB1 in clinical human lung tissue were assessed using bisulphite sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 28 publications
5
25
0
Order By: Relevance
“…In order to investigate the molecular mechanism of MDIG-promoted DDP resistance in lung adenocarcinoma cells, the present study examined the basal expression levels of efflux pump ABC transporters in A549 and A549/DDP cells, and it was revealed that the mRNA and protein expression levels of ABCB1, ABCC1 and ABCG2 in A549/DDP cells were significantly higher compared with those of A549 cells. This was consistent with previous studies (32)(33)(34), indicating that efflux pump ABC transporters are involved in DDP resistance in lung adenocarcinoma cells. To further investigate whether MDIG affected the resistance of lung adenocarcinoma to DDP by regulating the expression levels of the ABC transporter family, MDIG was overexpressed and silenced in A549 and A549/DDP cells, and the mRNA and protein expression levels of the ABC transporters were subsequently determined by RT-qPCR and western blot analysis, respectively.…”
Section: Discussionsupporting
confidence: 94%
“…In order to investigate the molecular mechanism of MDIG-promoted DDP resistance in lung adenocarcinoma cells, the present study examined the basal expression levels of efflux pump ABC transporters in A549 and A549/DDP cells, and it was revealed that the mRNA and protein expression levels of ABCB1, ABCC1 and ABCG2 in A549/DDP cells were significantly higher compared with those of A549 cells. This was consistent with previous studies (32)(33)(34), indicating that efflux pump ABC transporters are involved in DDP resistance in lung adenocarcinoma cells. To further investigate whether MDIG affected the resistance of lung adenocarcinoma to DDP by regulating the expression levels of the ABC transporter family, MDIG was overexpressed and silenced in A549 and A549/DDP cells, and the mRNA and protein expression levels of the ABC transporters were subsequently determined by RT-qPCR and western blot analysis, respectively.…”
Section: Discussionsupporting
confidence: 94%
“…Our results revealed significantly higher levels of ABC transporters in ovarian and endometrial cancer cells. These findings are consistent with previous studies [53][54][55], suggesting that the efflux pump ABC transporters are involved in DDP resistance in cancer cells. Additionally, following the treatment of cancer cells with progesterone-calcitriol combination, the expression levels of ABC transporters were significantly lower compared to the control cells.…”
Section: Discussionsupporting
confidence: 94%
“…Thirty-one studies have investigated the downstream region (DSR) of ABCB1 ( Figure 1 ). Among them, seven studies have targeted each of the 66 CpGs in the ABCB1 downstream promoter by BS [ 126 , 127 , 128 , 129 , 130 , 131 , 132 ]. Other studies applying BS have targeted 56 [ 133 ], 25 [ 134 ], 19 [ 135 ], or eleven [ 136 , 137 ] CpGs.…”
Section: Dna Methylation Analysis Of Abc Transporters In Cancermentioning
confidence: 99%